Persistence of the dominant soil phylum Acidobacteria by trace gas scavenging - Greening, Chris (Proc Natl Acad Sci U S A, 2015)
The majority of microbial cells in global soils exist in a spectrum of dormant states. However, the metabolic processes that enable them to survive environmental challenges, such as nutrient-limitation, remain to be elucidated. In this work, we demonstrate that energy-starved cultures of Pyrinomonas methylaliphatogenes, an aerobic heterotrophic acidobacterium isolated from New Zealand volcanic soils, persist by scavenging the picomolar concentrations of H(2) distributed throughout the atmosphere. Following the transition from exponential to stationary phase due to glucose limitation, the bacterium up-regulates by fourfold the expression of an eight-gene operon encoding an actinobacteria-type H(2)-uptake [NiFe]-hydrogenase. Whole-cells of the organism consume atmospheric H(2) in a first-order kinetic process. Hydrogen oxidation occurred most rapidly under oxic conditions and was weakly associated with the cell membrane. We propose that atmospheric H(2) scavenging serves as a mechanism to sustain the respiratory chain of P. methylaliphatogenes when organic electron donors are scarce. As the first observation of H(2) oxidation to our knowledge in the Acidobacteria, the second most dominant soil phylum, this work identifies new sinks in the biogeochemical H(2) cycle and suggests that trace gas oxidation may be a general mechanism for microbial persistence.